Influenza D Virus in Cattle and Swine in Piedmont Region, North-Western Italy. (March 2022) - Sparasci, O.A.; Rizzo, F.; Marchino, M.; Cerutti, F.; Guglielmetti, C.; Grosjacques, F.; Muratore, E.; Sona, B.; Biolatti, P.; Peletto, S.; Masoero, L.; Acutis, P.; et al.
Abstract : Purpose: This study aimed to investigate the circulation of Influenza D Virus – IDV (a new genus of the Orthomyxoviridae family) in cattle and swine in Piedmont (Cuneo province) by active and passive surveillance and by a retrospective study on swine archived samples collected in the same area in 2014-2015. Methods & Materials: According to risk-based criteria, 103 cattle and 44 pig farms (both fattening and reproduction) were selected for the sampling of nasal swabs, lungs and oral fluids. In each farm, 15 to 30 nasal swabs were collected from both healthy and symptomatic subjects. RNA extraction was performed with an automatic Maxwell® RCS 48 Promega extractor according to the manufacturer specifications. Oral fluid collection from swine was carried out using cotton ropes and RNA was then isolated by phenol-chloroform extraction from supernatant. As for lungs, a portion of approximately 25 mg of tissue was extracted in phenol-chloroform. Finally, the retrospective study was carried out on RNA extracts from pig nasal swabs and lungs collected in 2014-2015, as part of another research project. RNAs were amplified by One Step RT-PCR for Influenza D using the protocol designed on the region of the gene encoding the Pb1 protein. Results: Between 2018 and 2020 more than 600 samples were collected from 48 cattle farms and 35 pig farms. A total of 482 bovine nasal swabs, 44 bovine lungs, 105 swine oral fluids and 75 pig nasal swabs were processed for the identification of IDV RNA. In the retrospective study, 857 swine nasal swabs and 22 lungs from 43 farms were tested for IDV. Preliminary results showed 7 cattle farms (4 fattening, 3 reproduction/dairy ones) and 1 pig breeding farm positive for IDV, from the active surveillance and the retrospective study, respectively. Furthermore, viral isolation from positive samples on MDCK cells is ongoing. Conclusion: Our study confirms the presence of IDV in Piedmont region, in Cuneo province. Positivity found mainly in cattle and mostly during winter supports the hypothesis that cattle are the main reservoir of the virus and that winter is the season with the highest risk of infection.